PERCEPTION OF THE LANDSCAPE PAINTING BY PUPILS: “BARRIER-FREE” AND “BARIER” VISUALISATION TECHNIQUES - Pozdeeva, Svetlana (Revista Inclusiones, 2020)
The article states a problem of traditional methods effectiveness for developing coherent written speech among children when describing paintings. The process of painting perception handling and text writing results in the insufficient attention to children’s live speech; their activities are guided by the teacher, and individual perception of a painting is blocked by “barriers”, such as rigid teacher instructions, sample descriptive texts, etc. The article presents an experimental technique, based on establishing open educational communication between the teacher and pupils at the lesson where primacy and value of the painting as a visual image is recognized. Content of three lessons taught in the third grade is presented. The lessons were based on describing two paintings “Spring. High water” and “March” by I. Levitan. The article represents the comparative analysis of children’s texts – painting descriptions – based on different techniques of visualization; the analysis pays attention to children’s speech format and content (vocabulary, part-of-speech diversity, figures of speech, size of text and sentences). The following results are presented: a) comparison of text drafts and final versions describing the painting “Spring. High water”; b) comparison of texts describing the paintings “Spring. High water” (“barrier-free” technique) and “March” (using the prepared text description as a “barrier”); c) analysis of pupils’ worksheets for comparing two paintings; d) analysis of individual memos “How to write a painting description essay”.